Longitudinal analysis of race-management strategies in a world-class 200-m freestyle swimmer: a case study - Loisel, C., Pla, R., Seifert, L. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To investigate race-management strategies over a longitudinal case study of one of the world`s best female swimmers of the 200-m freestyle to understand if only 1 race-management strategy allowed her to succeed or whether several profiles have been used over the 8 years of analysis.